N-Heterocyclic carbene platinum complexes encapsulated in lipid particles: a novel strategy to target cancer cells and cancer stem cells in glioblastoma - De Larrinoa, Patricia Fernandez; Kichler, Antoine; Dontenwill, Monique; Herold-Mende, Christel; Fournel, Sylvie; Frisch, Benoît; Bellemin-Laponnaz, Stéphane; Heurtault, Béatrice (RSC medicinal chemistry, 2025)
The properties against cancer cells and glioblastoma stem cells of a series of platinum NHC complexes in lipid formulations are reported. As these organometallic compounds show very promising biological activities using conventional formulations, i.e. by solubilization in a DMSO/water system, the challenge for a therapeutic application is to be able to make them biocompatible while retaining this activity. Herein with the aim of eradicating cancer cells and cancer stem cells from glioblastoma, a disease in need of new therapies, we studied the encapsulation of platinum compounds in either liposome or lipid nanocapsule formulations and investigated the physical and chemical stability of the resulting nano-objects. It was then demonstrated that in these lipid formulations, platinum complexes retained their cytotoxic activity on both cancer cells and cancer stem cells. The best candidate, i.e. triphenylphosphonium-functionalized platinum-based complex, was then used for in vivo studies on mice using a U87-MG glioblastoma model, with significant results in slowing tumor growth, in particular when comparing to oxaliplatin. Another key strength of this study is the preservation of the compound's anti-cancer activity within a lipid-based formulation, eliminating the need for DMSO as a solvent. The findings of this study signify a major advance in the field, particularly in light of the expanding body of research on organometallic complexes conducted under conditions that preclude direct clinical applicability.
Gesehen am 20.10.2025